Evaluation of silicon and polymer substrates for fabrication of integrated microfluidic microsystems for DNA extraction and amplification. - Gheorghe, M; Blionas, S; Ragoussis, J; Galvin, P (2006)
This paper is presenting two different alternatives for the DNA extraction and amplification that will be carried out by two competitive research projects developing bioanalytical microsystems with microfluidics. The first project will develop the microfluidics part on polymer material and the other one on silicon. The polymer approach is currently under development based on a modular microfluidic architecture aimed to simplify the process of designing and building such a microsystem device. A silicon alternative is about to start and is expected to decrease packaging costs of the microsystem allowing future manufacturability of the device.